2010
DOI: 10.1002/ajmg.a.33457
|View full text |Cite
|
Sign up to set email alerts
|

A de novo duplication of Xp11.22–p11.4 in a girl with intellectual disability, structural brain anomalies, and preferential inactivation of the normal X chromosome

Abstract: Only a small number of individuals with duplications within the proximal short arm of the X chromosome have been reported. The majority of patients have duplications encompassing Xp11-p21, or extend more distally into Xp22. We report on a female patient who presented within the first year of life with plagiocephaly, speech delay, and epilepsy. Brain MRI showed a relatively thin cerebral cortex, abnormal periventricular white matter, and abnormal vessels in the left inferior parietal region. Cytogenetic and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 21 publications
1
29
0
3
Order By: Relevance
“…None of these genes escape X‐chromosome inactivation [Carrel and Willard, ; Zhang et al, ], thereby they are probably in functional disomy in these patients. This duplication occurs with higher incidence and a larger size in females, ranging from 0.3 to 4.4 Mb in males and from 4.5 to 12.3 Mb in females [Holden et al, ; Nizon et al, ].Consistent with our results, in all de novo cases in which the parental origin was verified, the duplication originated from the paternal X‐chromosome. On the other hand, all inherited duplications had a maternal origin, giving rise to familial cases [Evers et al, ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…None of these genes escape X‐chromosome inactivation [Carrel and Willard, ; Zhang et al, ], thereby they are probably in functional disomy in these patients. This duplication occurs with higher incidence and a larger size in females, ranging from 0.3 to 4.4 Mb in males and from 4.5 to 12.3 Mb in females [Holden et al, ; Nizon et al, ].Consistent with our results, in all de novo cases in which the parental origin was verified, the duplication originated from the paternal X‐chromosome. On the other hand, all inherited duplications had a maternal origin, giving rise to familial cases [Evers et al, ].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, all inherited duplications had a maternal origin, giving rise to familial cases [Evers et al, ]. Specific factors might be associated with instability in spermatogenesis giving rise to this duplicated chromosome, explaining why most patients are females [Holden et al, ]. Another possible hypothesis is that some female carriers can dose compensate the genomic imbalance by preferential inactivation of the aberrant X‐chromosome, causing a normal or mild phenotype and transmitting this imbalance to the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, small duplications of the proximal short arm of the X chromosome, in particular duplications encompassing Xp11.23, have been reported to be associated with neurodevelopmental disorders both in males and females [Bonnet et al, ; Froyen et al, ; Marshall et al, ; Monnot et al, ; Giorda et al, ; Holden et al, ; Chung et al, ; Edens et al, ; El‐Hattab et al, ]. Surprisingly, and in contrast to previously described larger duplications in Xp with selective inactivation of the aberrant X‐chromosome and a commonly normal phenotype in most carrier women [Matsuo et al, ], females with microduplications including Xp11.23 repeatedly showed preferential inactivation of the normal X‐chromosome.…”
Section: Introductionmentioning
confidence: 98%
“…This individual was described as having ID (IQ of 68), mild receptive and expressive language delay, moderate speech delay, autism, dysmorphic features, and severe hypotonia. Holden et al, [] reported a girl with de novo duplication at (40.4–52.7 Mb), described as having EEG abnormalities, brain MRI abnormalities, global developmental delay, expressive language delay, hypotonia, and indistinct speech.…”
Section: Discussionmentioning
confidence: 99%
“…Duplications involving HUWE1 (HECT, UBA, and WWE Domains‐Containing Protein 1) have been associated with non‐syndromic ID [Madrigal et al, ; Froyen et al, ] (MIM 300705). However, not all duplications of Xp11.22‐p11.23 in patients with ID include the HUWE1 gene, suggesting the involvement of other important ID genes in the Xp11.22‐p11.23 region [Giorda, ; Yan et al, ; Holden et al, ]. We report a cohort of 13 patients with overlapping Xp11.22‐p11.23 duplications to further study potential critical dosage‐sensitive genes in the region (Table ).…”
Section: Introductionmentioning
confidence: 94%